Speaking Out Feminism, Rape and Narrative Politics - Serisier, Tanya (Springer International Publishing, 2018)
This is the first critical study of feminist practices of 'speaking out' in response to rape. This book argues that feminist anti-rape politics are characterised by a belief in the transformative potential of women's personal narratives of sexual violence. The political mobilisation of these narratives has been an incredibly successful strategy, but one with unresolved ethical questions and political limitations. The book explores both the successes and the unresolved questions through feminist archival materials, published narratives of sexual violence, and mass media and internet sources. It argues that that a rethinking of the role and place of women's stories and the politics of speaking out is vital for a rethinking of feminist politics around sexual violence and key to fresh approaches to combating this violence.